Transport of Astyanax altiparanae Garutti and Britski, 2000 in saline water - Salaro, Ana Lúcia; Campelo, Daniel Abreu Vasconcelos; Tavares, Mateus Moraes; Braga, Luiz Gustavo Tavares; Pontes, Marcelo Duarte; Zuanon, Jener Alexandre Sampaio (Acta Scientiarum. Biological Sciences, 2015)
Two experiments were performed. The first aimed to assess the tolerance of fingerlings Astyanax altiparanae to water salinity. Fish were exposed to salinity of 0, 3, 6, 9, 12 or 15 g NaCl L-1 for 96 hours. The fish mortality was 0%, in the levels of 0, 3 and 6 g L-1; 75% in the level of 9 g L-1and 100% at 12 and 15 g L-1 of common salt. The second experiment aimed to assess the parameters of water quality, mortality and blood glucose during transport. For this, A. altiparanae were stored in plastic bags at 22, 30 and 37 g of fish L-1 stocking densities and salinity of 0, 3, 6 and 9 g L-1, for. Fish showed similar mortality levels in the different salinities and stocking densities. The increase in fish density reduced the dissolved oxygen levels and salinity decreased the pH. The blood glucose levels were higher in those fish with 0 g L-1 salinity and higher stocking densities. The addition of salt to the water reduces the stress responses of A. altiparanae during transport.